TAKHRIJ HADIS : METODE DEMONSTRASI DAN IMPLEMENTASINYA SERTA RELEVANSINYA DALAM DUNIA PENDIDIKAN - Rusmala Dewi, Diah; Nakiah, Nakiah; Ramadani, Tria (IAINU Kebumen Prodi IAT, 2024)
There are many hadiths related to the educational method that the Prophet has exemplified. However, in this article, we will focus on the discussion of the hadith about the demonstration method and its implementation as well as its relevance in today's education world. The method used is library research where the author tries to find, compile and analyze various hadith-related information about demonstration methods through various related sources, including through the hadith takhrij method using the Jawamiul Kalim application. The conclusions from this article are: (1) Based on the takhrij of the hadith that has been done, the hadith about the demonstration method in this article can be said to be an authentic hadith because it is proven to meet the requirements of the authenticity of a hadith, (2) The demonstration method is effective for aspects of education that aim to form specific skills (aspects of practical worship), (3) The relevance of the demonstration method in today's education contained in the 4 Pillars of UNESCO and the three aspects of student competence, which are found in the learning to do pillar which is a pillar related to the development of psychomotor aspects, that is, students can practice the basic ways of carrying out an act of worship practical or a life attitude.